THE APPOINTMENT OF MEMBERS TO THE SHARIAH ADVISORY COUNCIL OF CENTRAL BANK OF MALAYSIA: LEGAL ISSUES (UUM Journal of Legal Studies, 2017)
Abstract: In Malaysia, the appointment of members to the Shariah Advisory Council (SAC) of the Central  Bank  of Malaysia (CBM) is prescribed by the Central Bank of Malaysia Act 2009 (Act 701). The Act stipulates the provisions pertaining to the eligible persons to be appointed to the SAC, procedures, terms and conditions of appointment and also remuneration and allowances for the members of the SAC. In this regard, the question arises whether the prescribed provisions are sufficient to regulate the appointment of members to the SAC and free from any shortcomings. Hence, this study sought to analyse the existing legislations governing the appointment of members to the SAC and to analyse the legal issues arising from the existing legislations. By using legal research methodology, this article analysed the entire provisions dealing with the appointment matter. Based on the data collected from statutes passed by the Parliament of and Malaysia published materials, the analytical method was used by scrutinizing the related provisions of the law pertaining to the appointment of members to the SAC. This study found that, several loopholes  exist  in  the  statutory requirement of the existing law which needs to be addressed by the respective authoritative body in order to avoid any legal conflict in the future. Hence this study is significant in order to strengthen the existing legislation governing the SAC especially related the appointment process. Keywords: Shariah advisory council, Shariah advisor, Islamic finance, Islamic law, Central Bank of Malaysia Act 2009. Abstrak: Di Malaysia, pelantikan anggota Majlis Penasihat Shariah (MPS) Bank Negara Malaysia (BNM) ditetapkan oleh Akta Bank Negara Malaysia 2009 (Akta 701). Akta menetapkan peruntukan-peruntukan berkaitan orang yang layak untuk dilantik menganggotai MPS, prosedur, terma dan syarat-syarat perlantikan dan juga saraan dan elaun anggota-anggota MPS. Dalam hal ini, persoalan timbul sama ada peruntukan yang ditetapkan memadai untuk mengawal selia pelantikan anggota MPS dan bebas daripada sebarang kekurangan. Kajian ini bertujuan untuk menganalisis undang-undang sedia ada yang mentadbir pelantikan anggota MPS dan untuk menganalisis isu-isu undang-undang yang timbul daripada undang-undang sedia ada. Dengan menggunakan metodologi penyelidikan undang-undang, artikel ini menganalisis keseluruhan peruntukan yang berkaitan urusan pelantikan anggota MPS. Berdasarkan data yang telah kumpul daripada statut-statut yang diluluskan oleh Parlimen Malaysia, kaedah analisis telah digunakan dengan meneliti peruntukan-peruntukan undang-undang yang berkaitan pelantikan anggota MPS. Kajian ini mendapati bahawa, beberapa kelemahan wujud dalam kehendak statut dalam undang-undang sedia ada yang perlu diberi perhatian oleh pihak berkuasa yang berkaitan dalam usaha mengelak daripada berlaku sebarang konflik undang-undang pada masa hadapan. Oleh itu, kajian ini adalah sangat penting untuk mengukuhkan undang- undang sedia ada yang mengawal selia MPS terutamanya berkaitan proses pelantikan. Kata kunci: Majlis Penasihat Shariah, Penasihat Shariah, Kewangan Islam, Undang-undang Islam, Akta Bank Negara Malaysia 2009.